2019
DOI: 10.1371/journal.pone.0220458
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacist-led academic detailing improves statin therapy prescribing for Malaysian patients with type 2 diabetes: Quasi-experimental design

Abstract: ObjectivePrevious reports have highlighted the suboptimal utilization and prescription of statin therapy among patients with type 2 diabetes mellitus (T2DM) in the Malaysian clinical practice. This study aims to test the impact of a pharmacist-led academic detailing program on improving the overall statin therapy prescribing in Malaysian hospital and primary care settings.MethodsAs a quasi-experimental design with a control group and pre-tests., we examined 1,598 medical records of T2DM subjects in six healthc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Overall, as pharmacotherapy’s optimization is not a one-time intervention in people with chronic diseases, continuous assessments of the effectiveness and safety alongside interventions to boost adherence are increasingly needed to improve clinical outcomes [ 54 , 60 ]. Further detailed evaluations of the ongoing prescribing patterns will provide a basis for interventions that are most likely to be adopted in clinical practice [ 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, as pharmacotherapy’s optimization is not a one-time intervention in people with chronic diseases, continuous assessments of the effectiveness and safety alongside interventions to boost adherence are increasingly needed to improve clinical outcomes [ 54 , 60 ]. Further detailed evaluations of the ongoing prescribing patterns will provide a basis for interventions that are most likely to be adopted in clinical practice [ 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research highlighted that pharmacist-led interventions were associated with improvement in the rational use of hyperlipidemia medications. 30 Approximately 65% of the studies included in this review reported a significant impact of the pharmacist interventions on medication adherence by patients. Three studies were assessing medication adherence as secondary outcome measures.…”
Section: Discussionmentioning
confidence: 99%
“…A major cause is atherogenic dyslipidemia in T2DM, which consists of elevated triglyceride levels, decreased high-density lipoprotein (HDL), and a higher proportion of smaller and denser low-density lipoprotein (LDL) particles, which are more susceptible to oxidation and may thereby increase the risk of cardiovascular events [ 4 , 5 ]. Optimizing lipid-lowering therapy use among type 2 diabetic patients has been considered one of the beneficial approaches to decreasing the overall cardiovascular disease burden [ 6 ]. In T2DM patients, statin treatment is a cornerstone of the physicians' efforts to prevent primary and secondary cardiovascular disease [ 7 ].…”
Section: Introductionmentioning
confidence: 99%